List of Death of ‘Military Engineering’ Officers from Kozelsk and Starobielsk, Shot by the Soviet Union in April and May of 1940 - Cutter, Zdzisław (Social consequences of war, 2024)
Our knowledge about the Katyn crime is extensive, but many problems require clarification. One of them is the issue of Polish officers interned in the Soviet Union in 1939–1940. It is particularly important to present the full picture of the crime and the real truth about the fate of prisoners from three special camps in Kozielsk, Starobielsk and Ostashkov. These officers also included command and staff of military engineering, including 195 in Kozelsk and 129 in Starobielsk. At the same time, between April and May 1940, 16 officers were in the first camp and 25 officers in the second camp. Ultimately, it can be assumed that 332 military engineering officers were murdered in the Soviet Union. Their only fault was that they were outstanding citizens of the Republic of Poland and fell victim to a totalitarian system on an inhuman land.